An Unusual Diagnosis at Neck: Pilomatricoma in a Young Female: A Case Report (Journal of Shaheed Suhrawardy Medical College, 2022)
To be true, the name of this specific pathological lesion is not widely encountered in our dayto- day surgical practice, but still, pilomatricoma or pilomatrixoma is notifiable skin neoplasm for which diagnosis can be made histopathological and only after an adequate excision. This case report is of a 23-year-old young female medical student who presented with swelling in neck, that histopathologically diagnosed as pilomatricoma. The purpose of reporting this specific case is that this pathology is rare in occurrence, but more rarely diagnosed because of lack of confirmatory pathological analysis and it is immensely essential to be kept in the differentials of all superficial skin tumors in surgical practice.J Shaheed Suhrawardy Med Coll 2021; 13(1): 86-88